PCCC MC-CDMA COMBINATION PERFORMANCE OVER MULTIPATH RAYLEIGH FADING CHANNEL (Journal of Engineering, 2010)
his work presents the simulation of a Parallel Concatenation Convolution Coding PCCC with Multi-Carrier Code Division Multiple Access (MC-CDMA) system over multipath fading channels with a comparison with the uncoded data and that uses Serial Concatenated Convolutional Coding SCCC. The decoding technique used in the simulation was iterative decoding since it gives maximum efficiency with six iteration. Modulation schemes that used are Phase Shift Keying (BPSK, QPSK and 16 PSK), along with the Orthogonal Frequency Division Multiplexing (OFDM). The channel models used are as specified in the Third Generation Partnership Project (3GPP) Technical Specification TS 25.101 v2.10 with a channel bandwidth of 5 MHz.It was noticed that there is an improvement in the performance of the use of the PCCC data over the SCCC and uncoded data of SNR by many dBs as summarized in table [2] but with 8 and 16 PSK modulation schemes with the multipath fading channel a convergence of the BER to 10 cannot be obtained and it remains fluctuating around BER of 10-2